Implementation Of Mobile Application-Based Health Education For Hypertension Prevention In Young Adults: A Literature Review - syah ariq zaidaan najich (Journal of Diverse Medical Research : Medicosphere, 2026)
Hypertension among young adults is increasing due to modern lifestyles, yet conventional health education is often ineffective for this digital-native generation. This narrative review summarizes evidence from 2020–2025 on the effectiveness of mobile application-based health education for improving hypertension prevention behaviors and lowering blood pressure in young adults. Fifteen publications (meta-analyses, RCTs, feasibility studies, and protocols) were reviewed, focusing on mHealth interventions incorporating education, self-monitoring, reminders, feedback, and behavior change techniques (BCTs). Most studies found that apps with interactive educational features, blood pressure monitoring, adaptive reminders, and personalized feedback improved sodium intake, physical activity, and medication adherence. Meta-analyses reported an average systolic blood pressure reduction of 4–6 mmHg compared to controls. The highest effectiveness was seen in multi-component interventions lasting 3–6 months that applied BCTs such as goal setting, performance feedback, and self-monitoring. In conclusion, mobile app-based education is effective for hypertension prevention in young adults when designed with BCT principles. Implementation in campus and workplace settings offers a pragmatic strategy to expand the reach of hypertension prevention for young populations.